Massage-like stroking produces analgesia in mice - Zachary M.S. Waarala; Logan Comins; Sophie Laumet; Joseph K. Folger; Geoffroy Laumet (Neurobiology of Pain, 2024)
Chronic pain treatment remains a major challenge and pharmacological interventions are associated with important side effects. Manual medicine treatments such as massage, acupuncture, manipulation of the fascial system (MFS), and osteopathic manipulative treatments produce pain relief in humans, but the underlying mechanism is poorly understood limiting leverage and optimization of manual medicine techniques as safe pain therapy. To decipher the physiological mechanisms of manipulative medicine treatments, we have established a preclinical model. Here, we established a murine model of massage-like stroking (MLS)-induced analgesia. We characterized that the analgesia effects were present in both sexes, and were independent of the experimenters, handling, consciousness, and opioid receptors. MLS alleviates thermal pain in naive mice and postoperative pain hypersensitivity. This novel model will allow discovery of the physiological mechanisms involved in MLS-induced analgesia and identification of new therapeutic strategies.